Repeat treatment of acute hereditary angioedema attacks with open-label icatibant in the FAST-1 trial - Malbrán, Alejandro (2014)
Hereditary angioedema (HAE) is characterized by potentially lifethreatening recurrent episodes of oedema. The open-label extension (OLE) phase of the For Angioedema Subcutaneous Treatment (FAST)-1 trial (NCT00097695) evaluated the efficacy and safety of repeated icatibant exposure in adults with multiple HAE attacks. Following completion of the randomized, controlled phase, patients could receive open-label icatibant (30 mg subcutaneously) for subsequent attacks. The primary end-point was time to onset of primary symptom relief, as assessed by visual analogue scale (VAS). Descriptive statistics were reported for cutaneous/abdominal attacks 1–10 treated in the OLE phase and individual laryngeal attacks. Post-hoc analyses were conducted in patients with ≥ 5 attacks across the controlled and OLE phases. Safety was evaluated throughout. During the OLE phase, 72 patients received icatibant for 340 attacks. For cutaneous/abdominal attacks 1–10, the median time to onset of primary symptom relief was 1·0–2·0 h. For laryngeal attacks 1–12, patient-assessed median time to initial symptom improvement was 0·3–1·2 h. Post-hoc analyses showed the time to onset of symptom relief based on composite VAS was consistent across repeated treatments with icatibant. One injection of icatibant was sufficient to treat 88·2% of attacks; rescue medication was required in 5·3% of attacks. No icatibantrelated serious adverse events were reported. Icatibant provided consistent efficacy and was well tolerated for repeated treatment of HAE attacks.